2022
DOI: 10.1016/j.ssmqr.2021.100031
|View full text |Cite
|
Sign up to set email alerts
|

Navigating family planning access during Covid-19: A qualitative study of young women’s access to information, support and health services in peri-urban Nairobi

Abstract: The COVID-19 response has profoundly affected women’s access to family planning services in Kenya. While prior studies have shown how the COVID-19 response created barriers to accessing family planning (FP) services, less is known about how the pandemic affected the normative influence that partners, peers, and health providers exert on women’s FP choices. In this qualitative study, we interviewed 16 women (aged 18–25 years), 10 men in partnerships with women, and 14 people in women’s social networks across 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 29 publications
1
19
0
4
Order By: Relevance
“…In Kenya, there are inequities in accessing and navigating digital spaces resulting in a digital divide between those who have access to technology and data (such as phones or laptops) and those who are not able to access digital spaces due to other factors such as wealth or digital literacy (World Bank, 2019 ; Yousef et al, 2021 ). The digital divide has been exacerbated during COVID-19 (Beaunoyer et al, 2020 ), where studies have found that those living in peri-urban or low-income settings face difficult choices between accessing technology to stay connected to social networks remotely and meeting other daily needs, such as purchasing food (Hassan et al, 2021a ). However, we found those able to access and navigate digital media spaces faced other barriers such as social stigma in accessing and sharing information on FP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In Kenya, there are inequities in accessing and navigating digital spaces resulting in a digital divide between those who have access to technology and data (such as phones or laptops) and those who are not able to access digital spaces due to other factors such as wealth or digital literacy (World Bank, 2019 ; Yousef et al, 2021 ). The digital divide has been exacerbated during COVID-19 (Beaunoyer et al, 2020 ), where studies have found that those living in peri-urban or low-income settings face difficult choices between accessing technology to stay connected to social networks remotely and meeting other daily needs, such as purchasing food (Hassan et al, 2021a ). However, we found those able to access and navigate digital media spaces faced other barriers such as social stigma in accessing and sharing information on FP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous interventions to improve access to FP information found that targeting the channels in which social networks communicate has been key to address misinformation about FP (Nazzar et al, 1995 ; Colleran and Mace, 2015 ; Boydell et al, 2020 ). Studies in Kenya point to the role of health care providers (Alege et al, 2016 ) and key influencers, such as close family and friends, as trusted sources of FP information (Hassan et al, 2021a ) 1 . As more young people have access to the internet, digital media and technology in Kenya, healthcare providers have turned to digital media to develop new ways of sharing credible FP information with multiple groups, with an emphasis on young people (Zhou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations